From the first to the third edition of WN: the evolution of Adam Smith's economic thought in his texts (Cultura Económica, 2021)
The publication of the Wealth of Nations (WN) in 1776 is usually considered one of the great milestones in the history of economic thought. However, Adam Smith made alterations and additions throughout various subsequent editions. Although there do not appear to be radical changes or major conceptual modifications in any of them in comparison to the approach made in the first edition, a careful look at the additions and alterations shows that Smith's thought seems to have evolved over the years. This is particularly significant in the case of the third edition, published in 1784, eight years after the first edition, and on which Smith worked with particular attention. In this essay I will concentrate on comparing the additions that Smith made in his defense of free trade in the third edition of WN. In my opinion, these additions reveal the intellectual evolution experienced by the Scotsman while he was working as Commissioner of Customs. I will not only compare the two editions of the work, but I will pay special attention to the Smith Correspondence. In his epistles, as I will try to show, it is possible to perceive the intellectual evolution that the Scotsman was going through and that led him to present this new edition of the work, revised and completed.
Keywords: WEALTH OF NATIONS - EDITIONS; ADAM SMITH - CORRESPONDENCE; SCOTTISH ILLUSTRATION; FREE TRADE